PENGARUH PRENATAL GENTLE YOGA TERHADAP TINGKAT KECEMASAN IBU HAMIL TRIMESTER III DI PMB M BOGOR TAHUN 2022 - Wijaya, Putri - (STIKES ADVAITA MEDIKA TABANAN, 2023)
Background: Maternal Mortality Rate continues to increase every year. Causes of maternal death occur during pregnancy and childbirth. Psychological factors such as anxiety are important things that can affect the pregnancy and childbirth process. Complications from anxiety increase the risk of fetal nerve development, uterine contraction stimulation, increased blood pressure, fear of childbirth to postpartum depression. Supported self-help in the form of Prenatal Gentle Yoga can reduce and prevent anxiety complications in pregnant women. Purpose: This study aims to determine the effect of Prenatal Gentle Yoga on the level of anxiety of pregnant women in the third trimester in the intervention group and the control group. Method: This quasi-experimental study used a pre and post test with control group design. The sample in this study amounted to 40 patients consisting of 20 patients in the experimental group and 20 patients in the control group. The sampling technique used total sampling. The research instruments consisted of prenatal gentle yoga observation sheets and HARS anxiety level questionnaires. Data were analyzed using paired t-test and Independent t-test to determine differences in behavioral scores between groups. Results: The average level of anxiety in the pretest intervention group was 21.40 and posttest 17.80. The average anxiety level in the pretest of the control group was 21.80 and the posttest was 23.25. Bivariate analysis showed that there was an effect of prenatal gentle yoga on the anxiety level of pregnant women in the third trimester at PMB M Bogor Regency in 2022 with a sig of 0.000 (p <0.05). Conclusion: Prenatal Gentle Yoga has an effect on reducing anxiety levels in pregnant women in the third trimester.